Judicial Review Peraturan Daerah Sebagai Instrumen Perlindungan Hak Asasi Manusia atas Kebebasan Beragama di Indonesia - IMAN RIFA'I (Jurnal Hukum Lex Generalis, 2025)
Freedom of religion constitutes a non-derogable human right guaranteed under the 1945 Constitution of the Republic of Indonesia and international human rights instruments. Nevertheless, within the practice of regional autonomy, various local regulations and executive regional policies continue to impose restrictions upon the exercise of religious freedom through discriminatory and disproportionate norms. This study aims to analyze the role of judicial review as an instrument for the protection of human rights against local regulations that potentially restrict freedom of religion in Indonesia. The research employs a normative juridical method through statutory and conceptual approaches by examining constitutional provisions, legislation, judicial decisions, and relevant academic literature. The findings demonstrate that judicial review has not been fully effective in providing substantive protection for freedom of religion, as judicial assessment remains predominantly oriented toward formal legality review. Furthermore, the application of the principles of proportionality, legitimate limitation, and nondiscrimination within judicial reasoning has not been implemented consistently. This study proposes a human rights–based model of judicial review integrating both formal and substantive examination simultaneously in order to strengthen the constitutional protection of freedom of religion in Indonesia.